Diversifikasi Produk sebagai Strategi Peningkatan Daya Saing: Studi Kasus pada Perusahaan X di Industri Gula Kelapa dan Minuman - Lestari Ningsih, Titin; Rosalind Angelina, Felicia (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2025)
The diverse demand from consumers with products made from coconut sugar and instant powder allows the company to meet their needs. This research aims to find out the company's diversification with the production of coconut sugar and instant powder drinks, the difficulties and how to overcome them. The type of data in qualitative research with a descriptive approach. Data collection techniques are observation, interviews, documentation. Observation by observing the environment and production process. Interviews were conducted with manager, production, and warehouse informants. Documentation by taking photos relevant to this research. The results showed that PT x has diversified its products with a wide variety of variants but is still experiencing difficulties. Demand is diverse but the availability of raw materials is limited, human resources are limited and production space is still narrow. Delays in delivery so that the company gets complaints from consumers. The company should accept orders according to or relevant to the availability of raw materials, machinery, production space, and resources it has.